2008
DOI: 10.1007/s00360-008-0252-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate balance in fat sand rats feeding on high and low calcium diets

Abstract: Oxalate reduces calcium availability of food because it chelates calcium, forming the sparingly soluble salt calcium-oxalate. Nevertheless, fat sand rats (Psammomys obesus; Gerbillinae) feed exclusively on plants containing much oxalate. We measured the effects of calcium intake on oxalate balance by comparing oxalate intake and excretion in wild fat sand rats feeding on their natural, oxalate-rich, calcium-poor diet with commercially-bred fat sand rats feeding on an artificial, calcium-rich, oxalate-poor diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…Our results reveal that the transplant of fecal microbial communities increased total oxalate degradation by more than threefold with a corresponding decrease in urinary oxalate excretion by 48 %. Our results are on par with other transplant studies involving O. formigenes , a species that requires oxalate as a carbon and energy source, which have yielded a reduction in urinary oxalate of 49–70% [36, 37]. …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results reveal that the transplant of fecal microbial communities increased total oxalate degradation by more than threefold with a corresponding decrease in urinary oxalate excretion by 48 %. Our results are on par with other transplant studies involving O. formigenes , a species that requires oxalate as a carbon and energy source, which have yielded a reduction in urinary oxalate of 49–70% [36, 37]. …”
Section: Discussionsupporting
confidence: 81%
“…The loss of the probiotic oxalate-degrading bacteria after the removal of dietary oxalate is in contrast to other mammals, such as fat sand rats ( Psammomys obesus ), sheep, and some humans, that harbor oxalate-degrading bacteria natively. In these mammals, the oxalate-degrading bacterial populations are maintained across generations, even when oxalate is removed from the diet [3739]. …”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to mammals that are natural hosts to oxalate-degrading bacteria, such as the animals in the current study, which maintain those populations and their associated functions across generations and respond to increasing dietary oxalate even after long periods of time without oxalate in the diet (38,48,49). The transient colonization of the oxalate-degrading bacteria following probiotic treatment suggests that these transplanted bacteria are unable to integrate successfully into a foreign community, implying that there are underlying mechanisms of support for these bacteria in their natural hosts.…”
Section: Discussionmentioning
confidence: 84%
“…Under such conditions, it would be advantageous for O. formigenes to have the ability to facilitate solubilization of dietary crystalline oxalate. Previous rodent studies suggested that oxalatedegrading organisms degrade calcium oxalate crystals (63,64); however, the mechanism by which this occurs is not known. In this study, O. formigenes-monocolonized mice excreted significantly more urinary calcium and phosphate than did germfree mice, which might be due to degradation of calcium oxalate and calcium phosphate crystals by O. formigenes and subsequent intestinal absorption of free calcium and phosphate.…”
Section: Discussionmentioning
confidence: 89%